Analisis Faktor 5C Yang Menyebabkan Kredit Bermasalah Pada Debitur Umur Dibawah 45 Tahun di PT Bank Negara Indonesia (Persero) Tbk Cabang Sengkang - Surdani Surdani; Abdul Rahman Kadir; Andi Aswan (Magister Management, Hasanuddin University, 2019)
This study aims to determine the effect of the 5C factor on non-performing loans in debtors under the age of 45 years at PT. Bank Negara Indonesia (Persero), Tbk Sengkang Branch. The research is a quantitative study using multiple regression analysis with the assistant of SPSS application software. Data was collected through questionnaires distributed to 45 respondent of debtors. Validity and reliability of the questionnaire are evaluated beforehand. Based on the results of the study, the variable character negatively affects non-performing loans, the capacity negatively affects non-performing loans, the condition of economy negatively affect non-performing loans, the collateral negatively affects non-performing loans, the capital negatively affects non-performing loans for debtors under 45 years at PT. Bank Negara Indonesia (Persero) Tbk Sengkang Branch.